Análisis económico-financiero del almacén credi-loja electrodomésticos de la ciudad de loja, periodo 2019-2020 - Alvarado Ontaneda, Gueyvi Shasmin (2022)
The Curricular Integration Work "ECONOMIC-FINANCIAL ANALYSIS OF THE CREDILOJA APPLIANCES WAREHOUSE OF THE CITY OF LOJA, PERIOD 2019-2020", was carried out in order to identify the real state in which the company is located, so as to identify the economic and financial position; and in this way to be able to issue conclusions and recommendations that contribute to the development and proper functioning of the commercial entity. To meet the general objective, the vertical and horizontal analysis of the financial statements was developed to determine their variations. The one that presents the greatest relevance within the statement of financial position was current assets with a percentage of 95.47% in 2019 and 92.95% in 2020 represented especially in the Inventories and accounts receivable account in the two periods, this because the main activity of the company is the purchase and sale of appliances. Likewise, the financial indicators were applied that allowed to know the liquidity, profitability, activity and indebtedness that the company has in the years investigated, with their respective interpretation. And finally, a financial analysis report was prepared that contains conclusions and recommendations that will allow wise and timely decisions to be made. The elaboration of the work both in its theoretical and practical part is based on the application of different methods, starting from the scientific method that is the basis of theoretical-practical research; followed are the deductive and inductive method with which the information collected was ordered from the general to the particular; The statistical method was also used that facilitated the obtaining of the data in a summarized way in tables and graphs thus allowing a greater understanding of the results and finally the analytical and synthetic method used to demonstrate the results of the calculations and in this way to be able to make conclusions and recommendations that allow the adequate decision making in the Commercial Company. At the end of the degree work, the final report of financial analysis was prepared in which conclusions of the results and recommendations of the shortcomings found are proposed, which will allow correct decisions to be made to improve business development and determine management strategies that allow the restoration of the economic and financial administration of the company